Association of Maternal Antiangiogenic Profile at Birth With Early Postnatal Loss of Microvascular Density in Offspring of Hypertensive Pregnancies. Issue 3 (September 2016) - Yu, Grace Z.; Aye, Christina Y.L.; Lewandowski, Adam J.; Davis, Esther F.; Khoo, Cheen P.; Newton, Laura; Yang, Cheng T.; Al Haj Zen, Ayman; Simpson, Lisa J.; O'Brien, Kathryn; Cook, David A.; Granne, Ingrid; et al.
Abstract : Offspring of hypertensive pregnancies are more likely to have microvascular rarefaction and increased blood pressure in later life. We tested the hypothesis that maternal angiogenic profile during a hypertensive pregnancy is associated with fetal vasculogenic capacity and abnormal postnatal microvascular remodeling. Infants (n=255) born after either hypertensive or normotensive pregnancies were recruited for quantification of postnatal dermal microvascular structure at birth and 3 months of age. Vasculogenic cell potential was assessed in umbilical vein endothelial cells from 55 offspring based on in vitro microvessel tube formation and proliferation assays. Maternal angiogenic profile (soluble fms-like tyrosine kinase-1, soluble endoglin, vascular endothelial growth factor, and placental growth factor) was measured from postpartum plasma samples to characterize severity of pregnancy disorder. At birth, offspring born after hypertensive pregnancy had similar microvessel density to those born after a normotensive pregnancy, but during the first 3 postnatal months, they had an almost 2-fold greater reduction in total vessel density (−17.7±16.4% versus −9.9±18.7%; P =0.002). This postnatal loss varied according to the vasculogenic capacity of the endothelial cells of the infant at birth ( r =0.49; P =0.02). The degree of reduction in both in vitro and postnatal in vivo vascular development was proportional to levels of antiangiogenic factors in the maternal circulation. In conclusion, our data indicate that offspring born to hypertensive pregnancies have reduced vasculogenic capacity at birth that predicts microvessel density loss over the first 3 postnatal months. Degree of postnatal microvessel reduction is proportional to levels of antiangiogenic factors in the maternal circulation at birth. Abstract : Supplemental Digital Content is available in the text.